Kemitraan Strategis Antar Stakeholder Dalam Pengembangan Desa Wisata Gubugklakah Kab. Malang, Jawa Timur - Herlan Suherlan; Nurdin Hidayah; Wientor Rah Mada; Mochammad Nurrochman; Budi Wibowo (Sekolah Vokasi, Universitas Gadjah Mada, 2020)
This study intends to obtain comprehensive information of strategic partnerships between stakeholders in the development of in the Gubugklakah Tourism Village, Malang Regency – East Java. This study uses a qualitative research design with a phenomenographic approach. Data collection was carried out by interviewing penta-helix stakeholders, observations to the potential tourism objects and how the implementation of partnership strategies there, and studying all documents related to Gubugklakah Tourism Village strategies and policies. The results showed that 1). the strategy & policy development direction of the Gubugklakah Tourism Village is to make the Tourism Village managed professionally using a business approach that involves all stakeholders in a penta-helix framework, with the ultimate goal of mutual prosperity; 2). stakeholder participation involved in the development of the Gubugklakah Tourism Village in the concept of strategic partnership has been going well which is characterized by cohesiveness based on the principle of mutual trust, openness, mutual need, and mutual benefit; 3). the efforts made in the problem of strategic partnership are applying the five concepts of tourism village management, namely leadership, profit sharing system, product innovation, partnership, and marketing through a personal and familial approach.